Temporal trends in cardiovascular care: Insights from the COVID-19 pandemic - Kodsi, Matthew; Bhat, Aditya (Frontiers in Cardiovascular Medicine, 2022)
In response to the ongoing COVID-19 pandemic, public health care measures have been implemented to limit spread of the contagion and ensure adequate healthcare resource allocation. Correlating with these measures are observed changes in the incidence and outcomes of cardiovascular conditions in the absence of COVID-19 infection. The pandemic has resulted in a reduction in acute coronary syndrome, heart failure and arrhythmia admissions but with worsened outcomes in those diagnosed with these conditions. This is concerning of an underdiagnosis of cardiovascular diseases during the pandemic. Furthermore, cardiovascular services and investigations have decreased to provide healthcare allocation to COVID-19 related services. This threatens an increasing future prevalence of cardiovascular morbidity in healthcare systems that are still adapting to the challenges of a continuing pandemic. Adaption of virtual training and patient care delivery platforms have been shown to be useful, but adequate resources allocation is needed to ensure effectiveness in vulnerable populations.